A circular RNA hsa_circ_0079929 inhibits tumor growth in hepatocellular carcinoma - Zheng H (Cancer Management and Research, 2019)
Huifei Zheng,1,* Tengfei Chen,2,* Chang Li,2 Chun Xu,2 Cheng Ding,2 Jun Chen,2 Sheng Ju,2 Zhiwei Zhang,2 Zhipan Liang,2 Zihan Cui,2 Jun Zhao2 1National Center for Liver Cancer, Eastern Hepatobiliary Surgery Hospital, Second Military Medical University, Shanghai, China; 2Department of Thoracic and Cardiovascular Surgery, The First Affiliated Hospital of Soochow University, Soochow University, Suzhou, Jiangsu, China *These authors contributed equally to this work Purpose: Most recently, circular RNAs (circRNAs) were considered playing regulatory roles in tumor initiation and development. The specific function of circRNAs in hepatocellular carcinoma (HCC) remains unknown. This study was designed to detect specific roles of a circRNA hsa_circ_0079299 in HCC.Methods: The expression of hsa_circ_0079299 in HCC and tumor cell lines was detected using quantitative PCR (qPCR). Cell proliferation, migration, cell cycle and apoptosis after overexpression of the circRNA were measured using cell counting kit-8 (CCK8) assay, colony formation, 5-ethynyl-2′-deoxyuridine (EdU) assay, wound healing assay, transwell culture system and flow cytometry. Western blotting assay detected the protein expression of PI3K/AKT/mTOR signaling pathway and cyclin B1 (CCNB1). Overexpression of the circRNA in vivo was measured by nude mice tumorigenesis.Results: The expression of hsa_circ_0079299 was lower in HCC tissues. Overexpression of hsa_circ_0079299 suppressed tumor growth in vitro and in vivo, retarded cell cycle progression while had no effect on cell migration and apoptosis. The inhibitory effect of hsa_circ_0079299 was partly mediated by PI3K/AKT/mTOR signaling pathway.Conclusion: Our study shows that tumor suppressive role of hsa_circ_0079299 in HCC provides new recognition of circRNAs in cancers. Keywords: cell proliferation, cell cycle, cyclin B1, liver cancer